The Strategy of Islamic Religious Education Teachers in Fostering Student Morals at Elementary School - Mardianto Mardianto; Lidra Agustina Tanjung; Fahri Agung Nasution; Fiki Robi Handoko Harahap; Vera Yunita Siregar; Silvi Rewita; Sabila Akbar (Jurnal Basicedu, 2023)
The major consideration for pupils during the learning process is morality. This study intends to outline the methods Islamic religious education (PAI) instructors use to boost the spirits of young students. The Mutiara Aulia Medan Sunggal IT Middle School served as the study's location. This study employs a qualitative methodology and a descriptive study design. School principals, PAI teachers, and three students serve as the research's primary data sources. Secondary data are gathered from books, notes, and pertinent scientific papers to supplement the primary data. using procedures such as document analysis, observation, and interviewing to gather research data. data analysis that includes data display, data reduction strategies, and conclusion-making. According to the study's findings, the PAI teachers used habituation techniques and contextual strategies to promote student values. The concrete form comprises prayer sessions before and after class, regular Al-Qur'an recitation exercises, and group prayers during all school-related events, all of which are intended to instill a religious outlook in students. Three things—the skill of PAI professors, proper facilities, and scheduled study time—support this approach. The absence of student knowledge and the surroundings around students who are not yet enthusiastic about worship behavior are both restricting factors.